Same-Day Cancellation is Higher in Outpatient Pars Plana Vitrectomy for Proliferative Diabetic Retinopathy - Xi C; Zhang Y; Yue J; Liu Y; Li M; Wang G (Dove Medical Press, 2022)
Chunhua Xi,1 Yi Zhang,1 Jianying Yue,1 Ying Liu,2 Ming Li,1 Guyan Wang1 1Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, Beijing, People's Republic of China; 2Operation Center, Beijing Tongren Hospital, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Guyan Wang, Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, 1 Dongjiaominxiang Road, Dongcheng District, Beijing, 100730, People's Republic of China, Tel +86-10-58268101, Email guyanwang2006@163.comPurpose: Safety and efficiency of ambulatory pars plana vitrectomy (PPV) for proliferative diabetic retinopathy (PDR) patients is worthy of attention, since patients always have severe systemic diseases. The purpose of this study was to compare the incidence of same-day cancellation of PPV for PDR between outpatients and inpatients and to analyze the causes of cancellations.Patients and Methods: This is a retrospective review of consecutive PPV procedures for PDR from January 2019 to April 2021 at either the ambulatory or the inpatient surgery center in an academic tertiary referral center. Data on patient surgery plan, same-day surgical cancellation and follow-up were recorded. Differences in cancellation rate and reasons for cancellation (e.g. medical factors, patient reasons and administrative problems) between outpatients and inpatients were compared.Results: In total, 1810 consecutive PPV procedures of 1367 patients were identified; 1509 (83.4%) were managed as inpatient surgeries and 301 (16.6%) as outpatient surgeries. The total same-day cancellation rate was 5.2% for all patients. Although outpatients were younger (51 years vs 52 years, P < 0.001), had less proportion of hypertension (60.5% vs 74.0%), coronary artery disease (10.0% vs 18.8%), renal insufficiency (9.3% vs 18.0%) and cerebrovascular diseases (1.0% vs 11.4%) (all P < 0.001), had less proportion of patients with ASA III status (14.9% vs 27.4%, P < 0.001), and had higher proportion of regional anesthesia with MAC (19.9% vs 5.0%, P < 0.001), the cancellation proportion was significantly higher for outpatients than inpatients (12.3% vs 3.8%, P < 0.001). Overall, the most common reason for surgical cancellation was medical factors, occurring more frequently in outpatients than inpatients (91.9% vs 68.4%, P = 0.012).Conclusion: Same-day cancellation is higher in outpatient pars plana vitrectomy for proliferative diabetic retinopathy. To reduce ambulatory surgery cancellations, it is important to strengthen the monitoring of preoperative systemic comorbidities and adjust medication if necessary.Keywords: ambulatory surgery, same-day surgery cancellation, proliferative diabetic retinopathy, safety, efficiency